Pengetahuan Masyarakat Nelayan Tentang Pelestarian Hutan Mangrove di Desa Torokeku Kecamatan Tinanggea Kabupaten Konawe Selatan - Dinda Putri Heningtyas; La Ode Topo Jers (JURNAL KABANTI: Kerabat Antropologi, 2024)
This study aims to determine and describe the knowledge of fishing communities about mangrove forests, how the causes of mangrove forest damage, and how mangrove conservation efforts. This research used a qualitative approach and qualitative descriptive method. Data tracking of local communities using ethnographic techniques, observation, and documentation. Mangrove data collection is done through field observation method (primary data) which aims to determine the existing mangrove forest area in Torokeku Village, Tinanggea District, South Konawe Regency. The data collected was then analyzed using Cognitive theory by Ward Goodenough. The results of this study indicate that: 1). The community's understanding of the benefits of mangroves varies greatly, but the most common is that they understand the benefits of mangroves as a home protector from sea waves, and a good growing place for various types of marine life such as fish and crabs, meeting their daily needs; 2). In general, the status of the Mangrove ecosystem in the study site has been degraded due to the conversion of the Mangrove forest area into a medium category through ponds or fish ponds.